Establishment and growth of Lippia gracilis Schauer cultivated under different in vitro conditions - Lazzarini, Luiz Eduardo Santos; Pacheco, Fernanda Ventorim; Santiago, Alexsandro Carvalho; Coelho, Adriane Duarte; BERTOLUCCI, SUZAN KELLY VILELA; Pinto, José Eduardo Brasil Pereira (Scientia Agraria Paranaensis, 2022)
Lippia gracilis Schauer (Verbenaceae), popularly known as alecrim de tabuleiro‖ is used in folk medicine to treat colds, coughs, sinusitis, bronchitis, headache and externally skin conditions, burns, wounds, and ulcers. The tissue culture method of micropropagation has produced the greatest impact on plant production. It allows large scale plant multiplication within short periods of time using a limited physical space during any season of the year. The objective of this study was to evaluate the explant type, its position and the culture medium used for the establishment and in vitro culture of Lippia gracilis. For the establishment experiment, the treatments were: two types of explants (apical and nodal) taken from two cultivation environments (field and greenhouse), and inoculated in two types of culture medium (MS and MS/2). In order to verify the influence of the explant position, the treatments consisted of explants horizontally or vertically inoculated. For the evaluation of sucrose in the culture medium, the concentrations of 7.5; 15; 30 and 60 g L-1 were tested, while for salt concentration, the treatments consisted of 4 different salt concentrations: ¼ MS; ½ MS; MS and 2MS. In all experiments, a completely randomized design was used. Half of the salt concentration and the use of explants from a greenhouse reduced the rates of contamination, oxidation, and necrosis in the in vitro establishment of Lippia gracilis. The sucrose concentration of 30 g L-1 and ½ MS culture medium showed the best growth results for the species. Although the production of dry matter was reduced in this concentration of salts, the plantlets were more vigorous to proceed to acclimatization. Explants from a greenhouse inoculated horizontally in ½ MS medium supplemented with 30 g L-1 of sucrose increase growth parameters and the multiplication rate in the in vitro propagation of L. gracilis.